2020
DOI: 10.3389/ffgc.2020.00093
|View full text |Cite
|
Sign up to set email alerts
|

Wood Decomposition After an Aerial Application of Hydromulch Following Wildfire in a Southern California Chaparral Shrubland

Abstract: Severe wildfire can affect many soil processes, especially organic matter (OM) decomposition. Organic mulches are often applied on steep slopes to mitigate soil erosion, but little is known about how these surface organic additions affect subsequent soil OM decomposition. In 2003 the Cedar Fire burned 110,000 ha in southern California chaparral shrubland, after which hydromulch was aerially applied to reduce soil erosion. Subsequently, we established a 5-year study to assess the effect of hydromulch on OM deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
3
7
0
Order By: Relevance
“…Similar to other studies, aspen stakes in and on this sagebrush-steppe soil generally lost mass at a faster rate than pine because aspen has lower stake cellulose:lignin and C:N ratios (Jurgensen et al 2006; Wang et al 2018). Wood decomposition in mineral soil was greater after prescribed burning than in adjacent unburned plots, and this is similar to other studies that examined wood decay following prescribed burns in forests (Page-Dumroese et al 2019) or prairie soils (O'Lear et al 1996) and after a wildfire in chaparral (Jurgensen et al 2020). There is little information on wood decay in sagebrush habitats; however, sagebrush wood can act as a sink for nutrients because of its slow decomposition rate (Rickard 1985).…”
Section: Discussionsupporting
confidence: 87%
“…Similar to other studies, aspen stakes in and on this sagebrush-steppe soil generally lost mass at a faster rate than pine because aspen has lower stake cellulose:lignin and C:N ratios (Jurgensen et al 2006; Wang et al 2018). Wood decomposition in mineral soil was greater after prescribed burning than in adjacent unburned plots, and this is similar to other studies that examined wood decay following prescribed burns in forests (Page-Dumroese et al 2019) or prairie soils (O'Lear et al 1996) and after a wildfire in chaparral (Jurgensen et al 2020). There is little information on wood decay in sagebrush habitats; however, sagebrush wood can act as a sink for nutrients because of its slow decomposition rate (Rickard 1985).…”
Section: Discussionsupporting
confidence: 87%
“…We also anticipated that higher air temperature would generally lead to greater decomposition of stakes regardless of where the wood stakes are placed (Brischke and Rapp, 2008;Risch et al, 2013;Finér et al, 2016;Fissore et al, 2016), but that soil temperature would be an even better predictor than air temperature for the mineral stakes. We expected precipitation to interact with air temperature as a controlling factor for decomposition, in particular, for stakes placed at the soil surface where high precipitation and warm temperatures should speed up decomposition (Jurgensen et al, 2020). However, we also expected higher mineral stake decomposition at sites with lower precipitation, as water retention by the mineral soil becomes much more important for decomposition processes at drier sites.…”
Section: Introductionmentioning
confidence: 91%
“…Subsequent results from individual studies or regional sites showed that buried wood stakes generally decomposed faster than when put on the soil surface (Risch et al, 2013;Page-Dumroese et al, 2019;Wang et al, 2019;Jurgensen et al, 2020). Climatic properties, more specifically, higher soil temperatures, and to a lower degree higher precipitation, but not air temperature, were found to be the drivers of these differences in decomposition in Swiss subalpine forests (Risch et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, the effects of other mulch materials with higher C:N ratios, like eucalypt bark strands, could take even longer to be perceived as they typically have lower degradation rates (Barreiro et al, 2016). The addition of mulch can induce a priming effect of soil OM, but under field conditions this effect can be difficult to identify due to a complex interplay of biotic and abiotic factors (Jurgensen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%